POSTPARTUM HIV CARE CONTINUUM OUTCOMES IN THE SOUTHEASTERN US - CHEN, Jane S. (AIDS, 2019)
OBJECTIVE: Evaluate postpartum HIV care outcomes. DESIGN: Prospective clinical cohort of women with HIV and a live birth at the University of North Carolina, 1996–2014. METHODS: We estimated two stages of the HIV care continuum in the first 24 months postpartum: care retention (≥2 visits per year, ≥90 days apart) and viral suppression (HIV RNA <400 copies/mL). Multivariable models were fit using logistic regression. RESULTS: Among 1416 women, 141 experienced a live birth at a median age of 28 years, with 74% virally suppressed at delivery. Among all women, 48% were retained in care and 25% maintained viral suppression for the first 24 months postpartum. Among women with available HIV RNA measures, 42% were suppressed at 24 months. HIV care retention estimates were stable across calendar years, but viral suppression rates at 24 months postpartum, among women with available HIV RNA measures, increased from 33% to 67% from 1996–2001 to 2009–2014 (P=0.04). Being ≥30 years old was positively, and receiving <12 weeks of antenatal ART was negatively, associated with HIV care retention at 24 months postpartum (adjusted odds ratio [AOR]: 2.41, 95% CI: 1.09–5.29 and AOR: 0.27, 95% CI: 0.08–0.86). Older maternal age and viral suppression at delivery were both positively associated with virologic suppression at 24 months postpartum (AOR: 2.52, CI: 1.02–6.22, and AOR: 6.42 CI: 1.29–31.97, respectively). CONCLUSION: HIV care continuum outcomes decrease substantially postpartum, with younger women and those with less antenatal HIV care less likely to successfully remain engaged in HIV care following childbirth.